GRAMMATICAL AND MECHANICAL ERRORS IN STUDENTS’ ENGLISH WRITING AT UNIVERSITAS PAHLAWAN TUANKU TAMBUSAI - Haris, Hannisa; Rani, Afriza Rahma (The Future of Education Journal, 2025)
Writing is a crucial aspect of English as a Foreign Language (EFL) learning, yet many students face difficulties in applying grammatical rules and writing mechanics. This research aims to analyze the types and frequency of grammatical and mechanical errors in the English writing of second-semester students in the Undergraduate Program in Elementary Teacher Education at Universitas Pahlawan Tuanku Tambusai. A qualitative descriptive method was used, involving 40 student writing samples selected through purposive sampling. Data were collected through document analysis and analyzed using descriptive statistics. The findings revealed a total of 78 grammatical and mechanical errors. The most frequent error types were capitalization (23.08%), verbs (16.67%), and nouns (10.26%). Errors also appeared in the use of pronouns, articles, adjectives, and prepositions. These results show that students still struggle with fundamental grammar and mechanics, especially in sentence structure. The research recommends more focused grammar instruction and writing practice to reduce errors and improve writing accuracy and fluency.